Formal Description of Trusted Bebavior Oriented Security System for Big Data - Zhi Yan; Jing Zhan (Dianxin kexue)
Usually the process of storing and analyzing with big data is under the framework of Hadoop within the environment of cloud computing while the risks of big data application on cloud derive from cloud service providers and remote users who access data without authorization. Based on the security issues of big data applying on cloud, a security system for big data oriented by trusted behavior was given. The system with Z formal specification was described and the definition of abstract behaviors which contains reading, updating, adding and deleting operation was given. According to the abstract behavior model, behaviors were divided into trusted behavior and malicious behavior and security analysis on each operation was given. By using Z／EVES tool verified and proved the correctness about the description.